Present and Future Potential Habitat Distribution of Carcharhinus falciformis and Canthidermis maculata By-Catch Species in the Tropical Tuna Purse-Seine Fishery under Climate Change - Lezama-Ochoa, Nerea; Murua, Hilario; Chust, Guillem; Van Loon, Emiel; Ruiz, Jon; Hall, Martin; Chavance, Pierre; Delgado De Molina, Alicia; Villarino, Ernesto (Frontiers in Marine Science, 2016)
By-catch species from tropical tuna purse seine fishery have been affected by fishery pressures since the last century; however, the habitat distribution and the climate change impacts on these species are poorly known. With the objective of predicting the potential suitable habitat for a shark (Carcharhinus falciformis) and a teleost (Canthidermis maculata) in the Indian, Atlantic and Eastern Pacific Oceans, a MaxEnt species distribution model (SDM) was developed using data collected by observers in tuna purse seiners. The relative percentage of contribution of some environmental variables (depth, sea surface temperature, salinity and primary production) and the potential impact of climate change on species habitat by the end of the century under the A2 scenario (scenario with average concentrations of carbon dioxide of 856 ppm by 2100) were also evaluated. Results showed that by-catch species can be correctly modelled using observed occurrence records and few environmental variables with SDM. Results from projected maps showed that the equatorial band and some coastal upwelling regions were the most suitable areas for both by-catch species in the three oceans in concordance with the main fishing grounds. Sea surface temperature was the most important environmental variable which contributed to explain the habitat distribution of the two species in the three oceans in general. Under climate change scenarios, the largest change in present habitat suitability is observed in the Atlantic Ocean (around 16% of the present habitat suitability area of Carcharhinus falciformis and Canthidermis maculata, respectively) whereas the change is less in the Pacific (around 10% and 8%) and Indian Oceans (around 3% and 2 %). In some regions such as Somalia, the Atlantic equatorial band or Peru’s coastal upwelling areas, these species could lose potential habitat whereas in the south of the equator in the Indian Ocean, the Benguela System and in the Pacific coast of Central America, they could gain suitable habitat as consequence of global warming. This work presents new information about the present and future habitat distribution under climate change of both by-catch species which can contributes to the development of ecosystem-based fishery management and spatially driven management measures.